A sex‐specific, COX‐derived/thromboxane receptor activator causes depolarization and vasoconstriction in male mice mesenteric resistance arteries. Issue 2 (4th May 2020) - Chen, Hua; Simonsen, Ulf; Aalkjaer, Christian
Abstract: We investigated whether sex differences exist in cyclooxygenase‐dependent effects on membrane potential and relaxation in mice mesenteric resistance arteries. Mesenteric small arteries of 9‐ to 12‐week‐old, male and female, wild‐type mice, db/+ mice and diabetic db/db mice were mounted in myographs for measurements of isobaric diameter and smooth muscle cell membrane potential. Acetylcholine caused smaller dilation of arteries from male db/+ mice compared to arteries from female db/+ mice. In the presence of the NO synthase inhibitor N ω ‐nitro‐L‐arginine methyl ester (L‐NAME), acetylcholine‐induced dilation of arteries from males increased in the presence of indomethacin and the COX‐1‐specific inhibitor FR122047. The presence of indomethacin was also associated with a more negative membrane potential in arteries from males. In arteries from db/db mice, no sex differences were seen. In arteries from male but not female wild‐type mice, the thromboxane receptor blocker SQ29, 548 increased relaxation to acetylcholine. In contrast to arteries from female mice, COX (most likely COX‐1)‐derived prostanoids and activation of thromboxane receptors counteract acetylcholine vasodilatation probably through increased smooth muscle depolarization in arteries from male mice. In mice with diabetes and pronounced endothelial dysfunction, inhibition of COX did not enhance acetylcholine vasodilatation.